Principal's Efforts in Improving Teacher Performance at the Elementary Education Level - Sri Wahyuni; Sri Wahyuni Nasir; Neliwati Neliwati (Jurnal Basicedu, 2023)
Principal leadership has a crucial and vital role in creating a conducive learning climate in schools, including improving teacher performance. This study aims to analyze the efforts of school principals in improving teacher performance at the basic education level. This research method is a qualitative type, with an analytical descriptive study method. Collecting research data using interviews, observation and documentation studies. Furthermore, the data were analyzed using data reduction techniques, data presentation and drawing conclusions. The results of this study found; (1) the principal's leadership skills in managing information and resolving conflicts between educators; (2) giving suggestions from school principals to teachers about the importance of educating and improving the competence of educators; (3) the efforts of the principal in meeting the needs of teachers to teach, the economic welfare and social welfare (career) of teachers; and (4) providing opportunities for teachers to attend training and continue their studies (education). Thus, it was concluded that the principal's efforts to improve teacher performance were carried out well in schools.